The Meaning And Symbol Of Dodol Dawet In The Javanese Traditional Wedding Procession In Balongmacekan Village, Tarik District, Sidoarjo Regency - Hidayati, Laila Nur; Sinduwiatmo, Kukuh (Procedia of Social Sciences and Humanities, 2024)
The Javanese traditional wedding tradition is one of the unique cultural heritage values that are present and developing in Indonesia. This research aims to discover the meaning and symbol of Dodol Dawet carried out during the Javanese traditional wedding procession in Balongmacekan Village, Tarik District, Sidoarjo Regency, East Java. The method in this study uses a phenomenological perspective with a qualitative approach. The subject of this research is the meaning and symbol of Dodol Dawet, while the object of this research is Javanese traditional marriage in Balongmacekan Village, Tarik District, Sidoarjo Regency. The informants in this study were five people, including makeup artists, cultural experts, guests, and Dodol Dawet tradition actors. Interviews with informants were carried out for data collection. The results of this study are Dodol Dawet the parents' readiness to release their children to go to the level of marriage with their partners and hoping to cooperate in family life. The relevance felt after the implementation is the strengthening of social bonds, increased cultural awareness, spiritual balance, and learning of life values such as loyalty, cooperation, and responsibility in family and marriage relationships